The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.celrep.2019.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Single mRNP Analysis Reveals that Small Cytoplasmic mRNP Granules Represent mRNA Singletons

Abstract: Graphical Abstract Highlights d Cytoplasmic YBX1_IMP1 mRNP granules are elongated and branched structures d mRNPs are formed at the nuclear pore and await translation d Small cytoplasmic IMP1 and YBX1 mRNPs are mRNA singletons SUMMARY Small cytoplasmic mRNP granules are implicated in mRNA transport, translational control, and decay. Using super-resolution microscopy and fluorescence correlation spectroscopy, we analyzed the molecular composition and dynamics of single cytoplasmic YBX1_IMP1 mRNP granules in liv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 62 publications
3
20
0
Order By: Relevance
“…However, the exact role of YB-1 in this process is unknown. Recently, it was found that even though YB-1 and IGF2BP1 do not interact directly, they bind the same mRNA molecules immediately after mRNA nuclear export [142].…”
Section: Yb Proteins In Mrna Stability Controlmentioning
confidence: 99%
“…However, the exact role of YB-1 in this process is unknown. Recently, it was found that even though YB-1 and IGF2BP1 do not interact directly, they bind the same mRNA molecules immediately after mRNA nuclear export [142].…”
Section: Yb Proteins In Mrna Stability Controlmentioning
confidence: 99%
“…2 and 34 molecules with a median of 5-8 (Mateu-Regué et al 2019). Each RNA-binding protein may recruit several effector proteins, thus generating a niche.…”
Section: Lu Lu-f1 Lu-f2 Lu-f3mentioning
confidence: 99%
“…It has long been thought that "mRNA regulons" exist, in which functionally related groups of mRNAs are coregulated (Keene 2007). However, there is recent evidence that cytoplasmic mRNP (messenger RNA nucleoprotein complex) granules consist of single mRNAs, which would preclude coregulation of mRNAs (Mateu-Regué et al 2019). However, formation of larger mRNA granules such as TIS granules that contain many mRNAs may enable the mingling of different mRNAs to allow coregulation as well as coor peritranslational protein complex assembly of transcripts that are translated in vicinity to each other (…”
Section: Lu Lu-f1 Lu-f2 Lu-f3mentioning
confidence: 99%
“…Super‐resolution microscopy has recently given a more detailed outline of pre‐translational mRNPs. In contrast to the spherical appearance (“granular”) derived from conventional confocal microscopy, Structured Illumination Microscopy has shown that pre‐translational mRNPs are branched and elongated structures, [ 12 ] ranging from 100 to 1000 nm in size. [ 13,14 ] The mRNPs are composed of a single mRNA and one or two handfuls of RBPs which is in fine agreement with their size.…”
Section: Architecture and Dimensions Of Cytoplasmic Mrnpsmentioning
confidence: 99%